A long terminal repeat retrotransposon of Schizosaccharomyces japonicus integrates upstream of RNA pol III transcribed genes. Issue 1 (December 2015) - Guo, Yabin; Singh, Parmit; Levin, Henry
Abstract Background Transposable elements (TEs) are common constituents of centromeres. However, it is not known what causes this relationship.Schizosaccharomyces japonicus contains 10 families of Long Terminal Repeat (LTR)-retrotransposons and these elements cluster in centromeres and telomeres. In the related yeast, Schizosaccharomyces pombe LTR-retrotransposons Tf1 and Tf2 are distributed in the promoter regions of RNA pol II transcribed genes. Sequence analysis of TEs indicates that Tj1 ofS. japonicus is related to Tf1 and Tf2, and uses the same mechanism of self-primed reverse transcription. Thus, we wondered why these related retrotransposons localized in different regions of the genome. Results To characterize the integration behavior of Tj1 we expressed it inS. pombe . We found Tj1 was active and capable of generatingde novo integration in the chromosomes ofS. pombe. The expression of Tj1 is similar to Type C retroviruses in that a stop codon at the end of Gag must be present for efficient integration. 17 inserts were sequenced, 13 occurred within 12 bp upstream of tRNA genes and 3 occurred at other RNA pol III transcribed genes. The link between Tj1 integration and RNA pol III transcription is reminiscent of Ty3, an LTR-retrotransposon ofSaccharomyces cerevisiae that interacts with TFIIIB and integrates upstream of tRNA genes. Conclusion The integration of Tj1 upstream of tRNA genes and the centromeric clustering of tRNA genes inS. japonicus demonstrate that the clustering of this TE in centromere sequences is due to a unique pattern of integration.